Estado actual de vulnerabilidad sísmica del edificio administrativo del campus Alpachaca de la Universidad Estatal de Bolívar. - Pazmino Alegria, Diana Angelita (2019)
This current research work titled “Actual situation about seismic vulnerability of Administrative Building of Alpachaca Campus from The State University from Bolivar” located in Che. Guevara Avenue and Gabriel Secaira Street of Guaranda city from Bolivar Province in order to verify the seismic situation about the vulnerability of the building system. For the development of the research work we have gotten a base in the methodology that our career determines and it is structured in five chapters: initiating with the problem's analysis, theoretical mark, methodological frame, finding or resulting analysis, recommendations and conclusions of the project. We used some instruments like a matrix or picture based on PNUD methodology (United Nations Plan Development), we applied the Hammer Test instrument “esclerometro” which serves to value the durability of the concrete about structural elements conforming the building system, furthermore, we got digital cameras in order to verify the field working, we hat gotten a word processor for redacting and writing the project, we used excel calculating sheets for resulting tabulations, pictures with their technical analysis of results, we also had gotten an AutoCAD program in order to elaborate the inform about structural components known like pilasters, girders, concretes and stairs with their evacuation symbols for going out. Lastly, we looked for bibliographic information in the libraries in order to clear concepts and definitions. We describe the structural physical variables and indicators of the building, then we specify the degree of seismic vulnerability of the building, we also incorporate recommendations to describe the degree of seismic vulnerability of the administrative building. Within the result of the first objective to obtain the physical vulnerability index against seismic hazard, we proceeded to multiply the value of the indicator by the weight of weight given to us by a final product the vulnerability index 14 points this indicates that it is a low value within the criteria of the level of vulnerability according to the methodology applied "PNUD". As a result of the field work taken on the structural system, pillars, beams, slabs and bleachers, with the esclerometro showed similar values beams. XVII For the fulfillment of the third objective, recommendations are made for each one of the objectives, beginning with the maintenance of the masonry, so cracks and cracks were observed, as well as a study of the soil and functioning of the drainages. foundation level of the sub-floor, also proposals for reinforcement in the structural elements especially in the beams.